An application of value stream mapping for turnaround maintenance in oil and gas industry: Case study and lessions learned - Wenchi, S.; Wang, J.; Wang, X.; Chong, Heap Yih (2015)
Turnaround maintenance (TAM) in oil and gas industry concerns significant endeavours that deal with inspections, scheduled cleaning, adjustments, repairs and replacements of part of a plant to ensure operational reliability. It involves labour and material-intensive activities, thus is of the essence to minimize the financial impact. However, relevant research revealed that current process improvement strategies for TAM are random, isolated and scattered, improving individual activities in schedules without a systemic consideration of the entire process. Value Stream Mapping (VSM), a process of mapping the material and information flows in a value stream through systematic data capture and analysis, has showed its benefits in identifying and eliminating waste under various circumstances. This paper uses a case-based approach to measure efficiency improvement in TAM activities through VSM. The TAM project for a selected Liquefied Natural Gas (LNG) refinery plant is selected and analysed as a case study. This paper develops a current state map and a future state map to explore the wastes and root causes. The case study reveals that although some challenges and limitations, VSM is feasible in TAM project to improve the efficiency by identifying wastes in process and guiding value improvement.